2021
DOI: 10.3233/nre-201569
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular, perceived exertion and affective responses during aerobic exercise performed with imposed and a self-selected intensity in patients with Parkinson’s disease

Abstract: BACKGROUND: Exercise with self-selected intensity (SSI) has emerged as a new strategy for exercise prescription aiming to increase exercise adherence in Parkinson’s disease (PD). OBJECTIVE: We compared the cardiovascular, perceived exertion and affective responses during traditional aerobic exercise and with SSI in PD. METHODS: Twenty patients with PD performed two aerobic exercise sessions in random order with an interval of at least 72 h between them: Traditional session (cycle ergometer, 25 min, 50 rpm) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…There were no significant differences in exercise intensity markers such as HR and RPE between the two sessions. This finding aligns with previous studies that reported similar results for self-selected and imposed exercise intensities in other populations 9,10. Furthermore, the majority of patients maintained an HR >50% of their estimated maximal HR during both sessions, consistent with a prior study11 of PAD patients with claudication symptoms who exercised at the pain threshold and demonstrated HR ranging from 60-82% of maximal HR during the exercise session.…”
Section: Discussionsupporting
confidence: 91%
“…There were no significant differences in exercise intensity markers such as HR and RPE between the two sessions. This finding aligns with previous studies that reported similar results for self-selected and imposed exercise intensities in other populations 9,10. Furthermore, the majority of patients maintained an HR >50% of their estimated maximal HR during both sessions, consistent with a prior study11 of PAD patients with claudication symptoms who exercised at the pain threshold and demonstrated HR ranging from 60-82% of maximal HR during the exercise session.…”
Section: Discussionsupporting
confidence: 91%
“…The present study analyzed psychophysiological responses in individual and small group aerobic training with prescribed and self-selected intensities. Corroborating our primary hypothesis, we found that the self-selected intensity compared to the moderate intensity prescribed in aerobic training did not present significant differences in HR, LACT, RPE, FAS, PACES, TS and TD (p>0.05) [22,23].…”
Section: Discussionsupporting
confidence: 70%
“…The intensity of aerobic exercise is related to the perception of pleasure or displeasure during exercise [8,10,13,22]. Such perceptions are expressed by the affective response, which appears to predict future participation in exercise programs [12].…”
Section: Discussionmentioning
confidence: 99%
“…All patients performed three experimental sessions (control [C], TRAD, and SSI), which were conducted in a random order and with an interval of at least 72 h between sessions, as previously described [22]. Before the sessions, patients were instructed not to exercise in the previous 48 h, to eat a light meal 2 h before, to avoid caffeinated beverages on the testing days, and to take their PD medication 30 min before the start of the sessions.…”
Section: Experimental Protocolmentioning
confidence: 99%